Nut Intake Among Overweight/Obese African-American Women in the Rural South - Sterling, Samara R. (Am J Health Behav, 2016)
OBJECTIVE: Nut consumption decreases risk for obesity and chronic diseases, which are prevalent among African-American women in the rural Southeast US. The quantity and quality of nut intake in this population is unclear. We examined the amount, source, and quality of nut consumption among overweight/obese African-American women in rural Alabama and Mississippi. METHODS: Two 24-hour dietary recalls were administered to 426 women. Mann-Whitney tests, t-tests, and linear regression models observed: differences in added sugar and sodium intake between nut consumers and non-consumers; differences in mean nut, added sugar, and sodium intake between stand-alone and incorporated nut sources; relationship between nut intake and added sugar and sodium intake. RESULTS: Forty-two percent of participants consumed nuts, and 16% met federal recommendations for nut intake. Nut consumption was mainly from incorporated sources (65%), which were higher in added sugar (p < .001) and sodium (p < .001), and lower in nut quantity (p < .001) than stand-alone sources. Nut consumers consumed more daily added sugar (p = .004) and sodium (p = .04) than non-consumers. CONCLUSION: Suboptimal quantity and quality of nut intake may impede the health benefits of nut consumption among African-American women in the rural South.